Building Organization and Employee Resilience in Disaster Contexts - Teng-Calleja, Mendiola (Archīum Ateneo, 2020)
Purpose This study explored the resilience-building initiatives of work organizations using the Johns Hopkins Resistance–Resilience–Recovery Model. It also determined how resilience-building initiatives increase organizational resilience and promote employee resilience. Design/methodology/approach The study employed an exploratory sequential mixed-methods approach. In Study 1, resilience-building initiatives of selected work organizations in the Philippines were determined through qualitative research. A survey questionnaire to determine the presence of resistance, resilience and recovery programs in organizations was developed based on the results of this qualitative study. In Study 2, the empirical relations of these initiatives to reported levels of perceived organizational resilience as well as individual employee resilience were determined through a quantitative survey among employees. Data was analyzed using structural equation modeling. Findings The findings of the study described resistance, resilience and recovery programs in work organizations. Results also supported the hypothesis that the presence of resilience-building initiatives contributes to organizational resilience, which in turn affects employee resilience. Research limitations/implications The relatively low contribution of organization initiatives on organization resilience suggests that other factors may need to be explored. Also, despite using a sequential mixed-method approach, conducting longitudinal studies in future research will provide more robust data on the impact of interventions on resilience. Practical implications Management may use the results in identifying initiatives that can increase resilience in their organizations. The tool created may be utilized in gathering data on initiatives and help those in-charge of disaster risk reduction and management build a business case on the importance of investing in resilience-building efforts. Originality/value The study identified resilience-building initiatives of work organizations in a country that regularly experiences disasters as well as demonstrated the utility of the Johns Hopkins Model as framework for resilience building in the workplace. A survey questionnaire to determine the presence of resistance, resilience and recovery programs in organizations was developed through the exploratory study (Study 1), and the contributions of these initiatives to resilience of employees and organizations were established in Study 2.